Salt essentials - Sebenik, Craig; Hatch, Thomas (Thomas S.) (O'Reilly, 2015)
Get a complete introduction to Salt, the widely used Python-based configuration management and remote execution tool. This practical guide not only shows system administrators how to manage complex infrastructures with Salt, but also teaches developers how to use Salt to deploy and manage their applications. Written by two Salt experts, this book provides the information you need to deploy Salt in a production infrastructure right away. You'll also learn how to customize Salt and use salt-cloud to manage your virtualization. If you have experience with Linux and data formats such as JSON or XML, you're ready to get started. Understand what Salt can do, and get a high-level overview of basic commands Learn how execution modules let you interact with many systems at once Use states to define how you want a host or a set of hosts to look Dive into grains and pillars, Salt's basic data elements Control your infrastructure programmatically by extending Salt Master's functionality Extend Salt with custom modules, the Jinja templating language, and Python scripts.